Superconvergence Analysis of Gradient Recovery Method for TM Model of Electromagnetic Scattering in the Cavity (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we consider the transform magnetic (TM) model of electromagneticscattering in the cavity. By the Polynomial Preserving Recovery technique,we present superconvergence analysis for the vertex-edge-face type finite element.From the numerical example, we can see that the provided method is efficient andstable.